2019
DOI: 10.1038/s41598-019-44175-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of oxytocin receptor (OXTR) rs53576 genotype and maternal postpartum depression on child behavioural problems

Abstract: Previous studies have reported interaction effects of oxytocin receptor genotype (rs53576) and environmental factors on mental health in youth. However, the findings are mixed, especially regarding the type of allele (i.e., A vs. G), and it remains unanswered whether such an interaction presents at an early stage of development. Thus, using a unique longitudinal birth cohort sample in Japan ( n = 568), we examined whether there was an effect of the interaction between the OXT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…To date multiple efforts to unravel GxE interactions affecting depression-like behavior have been conducted, which demonstrated the interrelation of stress-related factors occurred at pre- and postnatal levels of development and OXTR gene polymorphisms. These studies reported a modulating effect of childhood adversity experienced by responders ( Park et al., 2019 ) or by their mother in childhood ( Elwood et al., 2019 ; Mileva-Seitz et al., 2013 ), maternal postnatal depression ( Choi et al., 2019 ), and even their child's OXTR genotype ( Asherin et al., 2019 ). Previously, an interaction between OXTR rs2254298 and the quality of the parental environment was reported to affect symptoms of depression and anxiety in female adolescents ( Thompson et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date multiple efforts to unravel GxE interactions affecting depression-like behavior have been conducted, which demonstrated the interrelation of stress-related factors occurred at pre- and postnatal levels of development and OXTR gene polymorphisms. These studies reported a modulating effect of childhood adversity experienced by responders ( Park et al., 2019 ) or by their mother in childhood ( Elwood et al., 2019 ; Mileva-Seitz et al., 2013 ), maternal postnatal depression ( Choi et al., 2019 ), and even their child's OXTR genotype ( Asherin et al., 2019 ). Previously, an interaction between OXTR rs2254298 and the quality of the parental environment was reported to affect symptoms of depression and anxiety in female adolescents ( Thompson et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since an interaction between childhood maltreatment and OXTR methylation at multiple CpG sites predicted depressive symptoms later in ontogenesis (Misra et al, 2019;Smearman et al, 2016), it was suggested that OXTR methylation might moderate, rather than mediate, the association between childhood abuse and depression (Park et al, 2019). According to previous research consistent with a diathesis-stress model (Augustine et al, 2018), rs53576 A-allele was frequently associated with psychopathologies correlated with an increased sensitivity to stress (Saphire-Bernstein et al, 2011;Choi et al, 2019). Despite the suggestion that individuals homozygous for the G-allele may exhibit greater sensitivity to social experiences (Asherin et al, 2019), the present findings oppositely demonstrated that A-allele carriers appeared to be more sensitive to parenting style (presumably, to the level of paternal interest in their lives) compared to those with GG genotypes.…”
Section: Oxytocin Receptor Genementioning
confidence: 99%
See 1 more Smart Citation
“…Maternal OXTR_rs53576 genotype was not assessed. Choi, Tsuchiya, and J., & Nori, T. () reported that behavioral difficulties in Japanese 6‐year‐olds whose mothers had experienced postpartum depression were significant only in children with the OXTR_rs53576 AA genotype. Kryski, Smith, Sheikh, Singh, and Hayden () showed that 3‐year‐olds with the OXTR_rs53576 AA genotype exhibited significantly more negative emotionality and behavior than those with at least one G allele, and further that negative infant behavior mediated the relation between infant genotype and lower parenting competence.…”
Section: Introductionmentioning
confidence: 99%
“…These data correlate with the results of our study, which show relatively greater emotionality -in some cases, reaching problematic degree -in adolescents with genotypes corresponding to high production and reception of OT. Choi et al [48] showed that the carriage of the A allele of OXTR rs53576 in a homozygous state, in combination with the occurrence of postpartum depression in the mother, was associated with a high risk of conduct problems and hyperactivity in 6-year-old children. In our study, no association was found between the carriage of the OXTR rs53576 A allele and conduct problems in adolescents.…”
Section: Discussionmentioning
confidence: 99%